Curcumin inhibited the growth and invasion of human monocytic leukaemia SHI-1 cells in vivo by altering MAPK and MMP signalling. (1st January 2020) - Zhu, Guohua; Shen, Qun; Jiang, Hong; Ji, Ou; Zhu, Lingling; Zhang, Linyang
Abstract: Context: Curcumin, a polyphenolic compound extracted from the rhizome of the tropical plant Curcuma longa L. (Zingiberaceae), has been considered as a cancer chemopreventive drug by American National Cancer Institute. Objective: To examine the effect of curcumin on acute monocytic leukaemia SHI-1 cells in vivo . Materials and methods: The SHI-1 cells (1 × 10 6 cells in 0.1 mL PBS) were injected subcutaneously into the right flanks of the female SCID mice. Curcumin dissolved in olive oil (15 and 30 mg/kg) was administered (i.p.) to mice once a day for 15 days while the control group received olive oil injection. Tumour proliferation and apoptosis were examined by PCNA, TUNEL and cleaved caspase-3 staining. The expression of MAPK, NF-κB, MMP9, MMP2 and vimentin were confirmed by RT-PCR, immunohistochemistry or western blotting. Results: Administration of curcumin significantly inhibited tumour growth, as the tumour weight decreased from 0.67 g (control) to 0.47 g (15 mg/kg) and 0.35 g (30 mg/kg). Curcumin inhibited the expression of PCNA and increased the degree of TUNEL and cleaved caspase-3 staining in tumour tissue. The results of western blotting showed that curcumin treatment inhibited NF-κB and ERK signalling while activating p38 and JNK. Moreover, curcumin attenuated the mRNA transcription and protein expression of MMP2 and MMP9. Curcumin also suppressed the level of vimentin. Discussion and conclusions: Our study demonstrates that curcumin can inhibit the growth and invasion of human monocytic leukaemia in vivo, suggesting the possible use of curcumin for anti-metastasis in leukaemia and the value of determining its unique target.